2017
DOI: 10.1515/hukin-2017-0031
|View full text |Cite
|
Sign up to set email alerts
|

IL-6, Antioxidant Capacity and Muscle Damage Markers Following High-Intensity Interval Training Protocols

Abstract: The aim of this study was to investigate changes of 51 ± 0.63, 0.84 ± 0.34 and 1.80 ± 0.60 for the 15s/15s, 30s/30s and 60s/60s protocol, respectively) and myoglobin (1.11 ± 0.29, 0.45 ± 0.48 and 1.09 ± 0.22 for the 15s/15s, 30s/30s and 60s/60s protocol, respectively). There were no substantial between-trial differences in other biochemical variables. In conclusion, the 15s/15s and 60s/60s protocols might be preferred to the 30s/30s protocols in order to maximize the training stimulus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
46
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(50 citation statements)
references
References 37 publications
(50 reference statements)
3
46
0
1
Order By: Relevance
“…This finding is in accordance with previous studies that showed increased plasma TAC levels across a range of exercise modalities. 36 , 37 , 38…”
Section: Discussionmentioning
confidence: 99%
“…This finding is in accordance with previous studies that showed increased plasma TAC levels across a range of exercise modalities. 36 , 37 , 38…”
Section: Discussionmentioning
confidence: 99%
“…Cipyran and Cipyran et al suggested that work time of HIIT could differentiate the myocardial, inflammatory, and autonomic function changes to acute exercise [12,13]. Jones et al found that both 6 s and 30 s bouts of HIIT over 2 weeks matched for total work performed and work-to-rest ratio, compared to work time, showed no difference between the two groups [14].…”
Section: Introductionmentioning
confidence: 99%
“…Jones et al found that both 6 s and 30 s bouts of HIIT over 2 weeks matched for total work performed and work-to-rest ratio, compared to work time, showed no difference between the two groups [14]. Therefore, studies to identify the effects of HIIT have been examined [12][13][14], but the results of the studies showed inconsistent results because it is difficult to compare the effects of different work-to-rest ratios for HITT.…”
Section: Introductionmentioning
confidence: 99%
“…Exercise-induced muscle damage occurs following unaccustomed and/ or very vigorous exercise and the increased levels of CK and myoglobin rank among those signs of exercise-induced muscle damage 23 . The high-intensity character of HIIE can potentially lead to muscle fiber impairment which can be manifested by increases in of CK and myoglobin concentration in plasma 24,25 . To our knowledge, this is the first study that analyzed the acute effects of a calisthenics HICT on muscle injury markers such as myoglobin and CK.…”
Section: Discussionmentioning
confidence: 99%